Analisis Efektivitas Metode Activity Based Costing (ABC) Dalam Menentukan Harga Pokok Produsi Pada Toko Bahagia Aluminium di Maros - Zhalsabila Islamyah Mirza; Azwar Anwar; Samsinar (Jurnal Sistem Informasi, Akuntansi dan Manajemen, 2026)
This study aims to analyse the effectiveness of the Activity-Based Costing (ABC) method in determining the cost of goods manufactured at the Happy Aluminium Store in Maros. The data analysis used is Descriptive Quantitative. Data collection was conducted through interviews, documentation, and literature reviews. The ABC method was chosen because it is able to allocate overhead costs more accurately based on the activities that cause costs, in contrast to traditional methods that tend to only use one charging base. The results of this study indicate that the Activity Based Costing (ABC) method produces a lower and more realistic cost of goods manufactured compared to the traditional method. The cost of goods manufactured for display products based on the ABC method is Rp15,485,872, while the traditional method produces Rp15,492,513, with a difference of Rp6,641. This indicates that the traditional method tends to experience overcosting.